Diferença e identidade: análise discursiva critica e semiótica social da campanha Ser Diferente é normal e da série Qual é a diferença? Sobre a síndrome de Down. - Denise Giarola Maia (2018)
Downs syndrome is described as a genetic disorder caused by the presence of an extra chromosome in the cells of a person's body, causing an intellectual disability. Within our system of knowledge and belief, the person with Down is generally identified as "abnormal,""incapable," "dependent", "sick," and so on, as a result of having a different and deficient body, being this deficiency something undesirable that causes a disorder in ontological security (LE BRETON,[1953] 2007; DINIZ, 2007). These forms of representation and identification of the person with Down are inscribed in a biomedical discourse andengendered from a concept of "normality". They support a hegemonic matrix, in which only the non-disabled body would be able to work, to study, among others. Then, this implies in unequal relations of power capable to provoke exclusion of the person with Down from thesociety. However, nowadays there are institutions and movements involved in the struggle for inclusion of these people in order to guarantee their rights. In addition, the media, particularly television, has given visibility to the deficient body through the broadcasting of commercialsand social mobilization campaigns, as well as in its journalistic and entertainment programming. Down's syndrome is therefore a sociocultural problem, which can be problematized by the discourse, in which this syndrome is materialized; becoming a social problem partially discursive (FAIRCLOUGH, [1992] 2001, [2003] 2004; CHOULIARAKI eFAIRCLOUGH, [1999] 2001). In this present research, we aimed to investigate the forms of communication and representation used to construct the identity meanings of the person with Down in commercials of Ser diferente é normal campaign by Instituto MetaSocial and inthe series of reports Qual é a diferença? by Fantástico. These both audiovisual productions would have been produced to raise awareness of society and to bring another view at the difference and identity of person with Down. In this way, we guided our study by the following general problem: what are the political and ideological motivations underlying themeaning of the semiotic resources used to represent the identity of the person with Down? For doing this, we did the defragmentation of the tele-film material, organizing it into static images (frames), according to the space-time continuity of the scene (IEDEMA, 2011).Then,we analyzed the contributory modes of the kineikonic mode of moving image (BURN, 2013); it means that we analyzed these images concerning their representational, interactional, and compositional meanings (KRESS e VAN LEEUWEN, 1996, 2006). Simultaneously, we did the analysis of the identificational meaning referring to the verbal component (FAIRCLOUGH, 2003) and critical analysis of music (VAN LEEUWEN, 2012). The discourse presented in the campaign and in the series, despite seemingly denying the hegemonic vision of the "normal" body and bringing a positive discourse of inclusion, respect for the person with Down and defense of the right to difference; it is crossed by a notion of normality and values such as independence and productivity, without being questioned. Moreover, in this ideological discourse, there is a dissimulation (THOMPSON, [1990] 2011) that works to silence other realities and experiences of Down's syndrome, contributing to theexistence of a new dichotomy (SILVA, 2012): the normal and included person with Down and the abnormal and segregated person with Down.